Immunomodulation of the Tumor Microenvironment: Turn Foe Into Friend - Locy, Hanne; de Mey, Sven; de Mey, Wout; De Ridder, Mark; Thielemans, Kris; Maenhout, Sarah K. (Frontiers in Immunology, 2018)
Immunotherapy, where the patient’s own immune system is exploited to eliminate tumor cells, has become one of the most prominent new cancer treatment options in the last decade. The main hurdle for classical cancer vaccines is the need to identify tumor- and patient specific antigens to include in the vaccine. Therefore, in situ vaccination represents an alternative and promising approach. This type of immunotherapy involves the direct intratumoral administration of different immunomodulatory agents and uses the tumor itself as the source of antigen. The ultimate aim is to convert an immunosuppressive tumor microenvironment into an immunostimulatory one, enabling the immune system to eradicate all tumor lesions in the body. In this review we will give an overview of different strategies that can be exploited for in situ vaccination and their emerging role in the treatment of cancer patients.